HOXA-AS2 may predict the prognosis of solid tumors among Chinese patients: A meta-analysis and bioinformatic analysis - Wang, Qiang; Zhang, Wei; Deng, Chao; Lin, Shicheng; Zhou, Yejiang (Frontiers in Oncology, 2022)
Background HOXA cluster antisense RNA 2 (lncRNA HOXA-AS2) is a long noncoding RNA (lncRNA) that aberrantly expressed in various cancers and is closely associated with cancer progression. To overcome the limitation of small sample sizes that are inherent to single studies, a meta-analysis was conducted to explore the relationship between the expression level of HOXA-AS2 and cancer prognosis. Methods Correlational studies were retrieved by searching the databases of PubMed, Embase and Web of Science (up to August 10, 2022). The survival and prognosis data included overall survival (OS), and clinical parameters were gathered and analyzed. Results Eighteen publications with 1181 patients who were diagnosed with solid tumors were ultimately included. The results showed that, compared with patients with low HOXA-AS2 expression, patients with high HOXA-AS2 expression tended to have poorer overall survival (OS) (HR= 2.52, 95% CI 1.87-3.38, P < 0.01) and shorter disease-free survival (DFS) (HR=7.19, 95% CI 3.20-16.17, P < 0.01). In addition, elevated HOXA-AS2 expression indicated a larger tumor size (OR =2.43, 95% CI 1.53–3.88,P < 0.01), more advanced TNM stage (OR=3.85, 95% CI 2.79-5.31, P < 0.01), earlier lymph node metastasis (LNM) (OR = 4.41, 95% CI 3.05-6.39, P < 0.01) and distant metastasis (DM) (OR= 2.96, 95% CI 1.87-4.7, P < 0.01). Furthermore, HOXA-AS2 expression was notassociated with age (OR=1.15, 95% CI 0.90-1.47), gender (OR=1.16, 95% CI 0.89-1.53), or tumor differentiation (OR=1.21, 95% CI 0.56-2.63). Moreover, aberrant HOXA-AS2 expression was related to drug sensitivity in various types of cancers. Conclusion The overexpression of HOXA-AS2 predicted poor cancer prognosis in the Chinese population, including poor OS, DFS, TNM, LNM, and DM. HOXA-AS2 could serve as a promising prognostic biomarker and therapeutic target. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022352604.